GENDER JUSTICE DYNAMICS WITHIN THE FRAMEWORK OF ISLAMIC LAW: AN IN- DEPTH EXPLORATION OF CRITICAL TRENDS IN RECENT VERDICTS FROM RELIGIOUS COURTS - Nana Suryapermana; Muhammadong; Shohib Muslim; Asri Agustiwi; Desi Syamsiah (Adisam Publisher, 2024)
This paper undertakes a comprehensive exploration of gender justice dynamics within the framework of Islamic law, focusing on critical trends in recent verdicts from religious courts. Drawing upon a multidisciplinary approach, the study navigates through the historical, theoretical, and contemporary dimensions of gender justice, shedding light on the evolving interpretations and applications of Islamic legal principles. Case studies of significant recent verdicts offer in-depth analyses, unraveling the legal reasoning and broader implications for gender justice within diverse cultural contexts. The synthesis of findings provides a nuanced understanding of the complexities inherent in pursuing gender justice within the multifaceted landscape of Islamic law. This research contributes to academic discourse and offers insights for policymakers, practitioners, and scholars engaged in fostering equitable legal frameworks.